Close to you [videorecording (DVD)] - Savage, Dominic, 1962-; Page, Elliot, 1987-; Baack, Hillary; Outerbridge, Peter; Crewson, Wendy (Greenwich Entertainment, 2024)
Academy Awardʼ Nominee Elliot Page stars as a trans man who returns to his hometown for the first time in years. On his journey, he confronts his relationship with his family, reunites with a first love, and discovers a newfound confidence in himself.